2006
DOI: 10.1039/b603980d
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of α-chymotrypsin at air–water interface through surface binding to gold nanoparticle scaffolds

Abstract: Gold nanoparticles stabilize chymotrypsin (ChT) against denaturation at the air-water interface through catenation and preferential localization of the nanoparticles at the airwater interface with concomitant decrease in interfacial energy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 30 publications
2
27
0
Order By: Relevance
“…Stability of the gold solutions can be achieved by the introduction of molecules that interact with AuNPs through bonding and/or electrostatic interactions. 58,59 For this purpose, various biological probes have been used for the stabilization and/or functionalisation of colloidal AuNPs; these include nucleic acids, enzymes, receptors, lectins, antibodies and superantigens. [60][61][62][63][64]…”
Section: Colloidal Aunps Stabilizationmentioning
confidence: 99%
“…Stability of the gold solutions can be achieved by the introduction of molecules that interact with AuNPs through bonding and/or electrostatic interactions. 58,59 For this purpose, various biological probes have been used for the stabilization and/or functionalisation of colloidal AuNPs; these include nucleic acids, enzymes, receptors, lectins, antibodies and superantigens. [60][61][62][63][64]…”
Section: Colloidal Aunps Stabilizationmentioning
confidence: 99%
“…Further studies demonstrated that nanoparticle-protein complexation can considerably stabilize the bound proteins against denaturation at the air/water interface. [26] Specific biomacromolecular interactions such as streptavidin/biotin complementarity (K a $ 10 14 M…”
Section: Review Articlementioning
confidence: 99%
“…[2b,33] To examine the potential role of nanoparticle stabilisation of the functional protein in this work, we have generated and examined the impact of cellular exposure to particle formulations in which the protein was bound through a reductively [7b,27] or pH [4b,26] -cleavable linker, particle types (9) and (10). The pH or reductant-initiated cleavage of protein from these particles was initially confirmed (Figure S5 in the Supporting Information).…”
Section: Resultsmentioning
confidence: 99%